The effect of student acceptance on learning outcomes: AI-generated short videos versus paper materials - Yidi Zhang; Margarida Lucas; Pedro Bem-haja; Luís Pedro (Computers and Education: Artificial Intelligence)
The use of video and paper-based materials is commonly widespread in foreign language learning (FLL). It is well established that the level of acceptance of these materials influences learning outcomes, but there is lack of evidence regarding the use and related impact of videos generated by artificial intelligence (AI) on these aspects. This paper used linear mixed models and path analysis to investigate the influence of student acceptance of AI-generated short videos on learning outcomes compared to paper-based materials. Student acceptance was assessed based on perceived ease of use (PEU), perceived usefulness (PU), attitude (A), intentions (I), and concentration (C). The results indicate that both AI-generated short videos and paper-based materials can significantly enhance learning outcomes. AI-generated short videos are more likely to be accepted by students with lower pre-test scores and may lead to more significant learning outcomes when PEU, PU, A, I and C are at higher levels. On the other hand, paper-based materials are more likely to be accepted by students with higher pre-test scores and may lead to more significant learning outcomes when PEU, PU, A, I and C are at lower levels. These findings offer empirical evidence supporting the use of AI-generated short videos in FLL and provide suggestions for selecting appropriate learning materials in different FLL contexts.